Manajemen Mutu Berbasis Religi di SD Mutiara Parahyangan Bandung - Irwanto Sahidin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
This study discusses about religious-based quality management in Mutiara Parahyangan Elementary School, Bandung. Many cases of child mischief encourage schools to improve the quality of education through religious activities that can change the character of students. This study uses a descriptive qualitative approach. The data were collected through documentation, interviews, and observations. The results of the study show that the religious-based quality management concept is based on a commitment to improving the quality of education based on universal Islamic values. It is manifested in several activities are as follows, (1) The quality planning of vision, mission, and yearly semiannual programs, (2) The quality implementation in the form of religious activities that support religious practice in schools through routine, weekly, and monthly activities. (3) The quality evaluation is conducted periodically. (4) The quality control is carried out as a follow-up from the evaluation results to improve the quality. All of these activities always lead to the quality management principle of continuous improvement.